Critical success factors for Big Data adoption in the virtual retail: Magazine Luiza case study - Muniz Félix, Bruno; Tavares, Elaine; Cavalcante, Ney Wagner Freitas (Review of Business Management, 2017)
Purpose – The objective of this research was to identify critical success factors for the adoption of Big Data in the virtual retail, through a case study of Magazine Luiza. The use of Big Data, in this case, focused on improving its system of recommendations for a better understanding of consumer behavior. Design/methodology/approach – The case study was done through interviews, observation of the shopping recommendation system and analyzes of institutional presentations of the Bob project. A semistructured interview script was used in the interviews. Findings – Based on the results, we outline some propositions related to the opportunities and obstacles for the implementation of Big Data in the virtual retail in Brazil. Some of these propositions are in line with what literature, especially BI, has been discussing. However, they still need to be discussed in the context of Big Data. Originality/value – The main contribution of the research was the identification of relevant factors to the adoption of Big Data that were not considered as critical for the adoption of previous technologies.